Benefits of visibility in industrial construction projects: supply chain stakeholders’ perspectives - Dharmapalan, Vineeth; O’Brien, William J.; Morrice, Douglas (Frontiers in Built Environment, 2025)
IntroductionSupply Chain Visibility (SCV) is increasingly recognized as a critical enabler of effective material delivery, coordination, and risk management in industrial construction. However, the specific benefits of SCV and how they are perceived across stakeholder groups remain underexamined. This study provides an evaluation of SCV benefits from the perspective of owners, contractors, designers, and suppliers engaged in industrial construction projects.MethodsThirteen SCV benefits were identified through a detailed literature review and refined using structured expert workshops. These benefits were then evaluated through an industry survey (n = 165). The analysis used Relative Importance Index (RII) to rank the benefits, Kruskal–Wallis tests to assess between-group differences, and Percentage Agreement and Kendall’s tau rank correlation coefficient for the rank agreement analysis.ResultsThe results reveal broad agreement on the top SCV benefits, including risk mitigation, ability to track and trace materials, field installation productivity improvement, and improved delivery timing. Notably, traditionally emphasized benefits like lead time reduction were ranked lower, suggesting unique visibility needs in construction compared to other industries. Kruskal–Wallis tests found no median differences between the four groups (all p > 0.05). The percentage agreement patterns and the Kendall’s tau rank correlation coefficient results indicate that contractors play a central role in aligning upstream and downstream visibility needs (Owner–Contractor, PA = 64.63%, τ-b = 0.555, adjusted p-value <0.05; Contractor–Supplier, PA = 65.47%, τ-b = 0.578, adjusted p-value <0.05).DiscussionThe benefit rankings offer construction professionals a benchmark for prioritizing and communicating SCV initiatives. The results also inform more targeted visibility strategies tailored to the roles and priorities of different stakeholder groups. This study is among the first to define and assess SCV benefits across multiple construction stakeholder groups. It contributes to theory and practice by offering a stakeholder-informed foundation for evaluating SCV in industrial construction.